Sine-wave windowed synthesis - Gardzielewska, Hanna; Kaczmarek, T. (Archives of Acoustics, 2006)
Speech can be understood even when a 3-tone replica of speech is presented to a listener.In tonal synthesis, called sine-wave synthesis (SWS), the output signal consists of number oftime-varying sinusoids that follow center frequencies and amplitudes of the first number offormants of a natural utterance. In this paper we propose an alternative technique of speechsynthesis. It is based on the number of dominant frequency components present in the originalsignal. In the proposed method, called sine-wave windowed synthesis (SWWS), the amplitudesand frequencies of tonal components are changed in discrete steps in subsequent timewindows. Perceptual tests performed on Polish speech show that signals synthesized with theSWWS technique are judged as more natural and intelligible than SWS speech.